IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA NOMOR 12 TAHUN 2015 TENTANG PROGRAM INDONESIA PINTAR (PIP) DI DESA LALANG SEMBAWA KECAMATAN SEMBAWA KABUPATEN BANYUSIN - Annisa, Annisa (Jurnal Ilmiah Administrasi Dan Sosial, 2023)
The Smart Indonesia Program is very much needed by students who come from underprivileged/poor families, because students who come from poor families are very vulnerable to dropping out of school. Thisis due to the unsupportive economic situation of the student's family, so the student decides to quit school and chooses to work. The Smart Indonesia Card was launched by the government under the auspices of the Ministry of Education and Culture (Kemendikbud) through the National Team for the Acceleration of Poverty Reduction (TNP2K).The research objective to be achieved in this study is to analyze the implementation of the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 12 of 2015 concerning the Smart Indonesia Program (PIP) in Lalang Sembawa Village, Sembawa District, Banyuasin Regency. The data collection used by the author is by conducting interviews, observations and documentation studies. While the data analysis technique used is descriptive method with qualitative analysis The results of the research Implementation of the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 12 of 2015 concerning the Smart Indonesia Program (PIP) in Lalang Sembawa Village, Sembawa District, Banyuasin Regency has been carried out well, seen from the communication in the implementation of PIP carried out by giving notifications to the public. Implementing human resources both from the village and from the school are available. And judging from the second concept, if there are students who do not get PIP but have PKH, they can make suggestions to the village government. And an introduction will be made. At the Karya Sembawa High School, there were two students from Lalang Sembawa Village who became PIP recipients. Of the two students who are PIP recipients, they are not from PKH or KKS beneficiary famili. Keywords: Implementation and Smart Indonesia Program (PIP)